2005
DOI: 10.1007/s00122-005-2045-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of dry matter and nitrogen accumulation and protein composition in wheat kernels

Abstract: The maximum rate and duration for grain dry matter (DM) and nitrogen (N) accumulation were evaluated in 194 recombinant inbred lines (RILs) from a cross between the two French wheat cultivars Récital and Renan. These cultivars were previously identified as having contrasting kinetics of grain DM and N accumulation. Grain protein composition was analysed by capillary electrophoresis (CE), which enabled quantification of the different storage protein fractions (alphabetagamma-gliadins, omega-gliadins, LMW gluten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 45 publications
4
42
0
1
Order By: Relevance
“…However, the genetic control of whole-season N efficiency has rarely been examined in wheat. Recent extensive molecular studies (Charmet et al 2005;Quarrie et al 2005;Habash et al 2007;Laperche et al 2008;Fontaine et al 2009) identified numerous genome regions (QTLs) responsible for grain yield structure and nitrogen yield under N limitations, grain protein content and N metabolism in the uppermost foliage as well as for the activity of glutamine synthetase and glutamate dehydrogenase, the key enzymes involved in N assimilation. In earlier investigations (Le Gouis et al 2002), both additive and non-additive genetic effects were crucial for agronomic NUE components in F 1 hybrids between modern French cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…However, the genetic control of whole-season N efficiency has rarely been examined in wheat. Recent extensive molecular studies (Charmet et al 2005;Quarrie et al 2005;Habash et al 2007;Laperche et al 2008;Fontaine et al 2009) identified numerous genome regions (QTLs) responsible for grain yield structure and nitrogen yield under N limitations, grain protein content and N metabolism in the uppermost foliage as well as for the activity of glutamine synthetase and glutamate dehydrogenase, the key enzymes involved in N assimilation. In earlier investigations (Le Gouis et al 2002), both additive and non-additive genetic effects were crucial for agronomic NUE components in F 1 hybrids between modern French cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Significant quantitative genetic variations in GSP composition have also been reported for wheat (Graybosch et al, 1996;Huebner et al, 1997). However, only a few quantitative trait loci have been identified (Guillaumie et al, 2004;Charmet et al, 2005;Ravel et al, 2006c), and so far no gene or allele controlling natural variations in GSP composition has been identified.…”
mentioning
confidence: 99%
“…Proteinfraction and starch contents in wheat grains are affected by genes and environment. To date, many studies carried out on QTLs in wheat have focused on protein-fraction content, which are distributed on at least 15 chromosomes, such as 1A, 1B, 2A, 2B, 2D, 3A, 3B, 4A, 5B, 5D, 6B, 6D, 7A, 7B, and 7D chromosomes (Charmet et al 2005;Mann et al 2009;Merlino et al 2009;Zhang et al 2011). In the present study, atotal of 17 unconditional additive QTLs (four albumin QTLs, three globulin QTLs, six gliadin QTLs, four glutenin QTLs) controlling protein component content were detected.…”
Section: Discussionmentioning
confidence: 99%